2020
DOI: 10.1002/adem.202000315
|View full text |Cite
|
Sign up to set email alerts
|

Surface Defects Sensitivity during the Unfolding of Corrugated Struts Made by Powder‐Bed Additive Manufacturing

Abstract: Corrugated struts as part of lattice structures can lead to novel mechanical behavior by a combination of material and geometrical hardening. The unfolding behavior of such struts offers a potential of large macroscopic straining. However, their ability to be unfolded is impacted by the surface characteristics inherited from the additive manufacturing process. This study evaluates the unfolding sensitivity to these surface characteristics. Corrugated struts with varying surface roughness have been produced usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The second requirement is related to the geometrical characteristics of the corrugation (wavelength, thickness…) and the presence of surface notch-like defects. Strategies to ensure the unfolding of the corrugated struts were preliminary studied in [3] for the selection of the geometrical characteristics, and in [8] to evaluate the effect of surface defects. The geometrical features have to be selected appropriately because as-built parts made of Ti6Al4V exhibits a moderate elongation to failure (between 5 and 8%, see [16]) and this can lead to premature failure of the corrugated struts [3].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The second requirement is related to the geometrical characteristics of the corrugation (wavelength, thickness…) and the presence of surface notch-like defects. Strategies to ensure the unfolding of the corrugated struts were preliminary studied in [3] for the selection of the geometrical characteristics, and in [8] to evaluate the effect of surface defects. The geometrical features have to be selected appropriately because as-built parts made of Ti6Al4V exhibits a moderate elongation to failure (between 5 and 8%, see [16]) and this can lead to premature failure of the corrugated struts [3].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, surface defects were proven to be detrimental for the mechanical properties, in particular for the fatigue life [15] but also in term of ductility (elongation-to-failure) [16]. The population of residual surface defects along single struts after chemical etching as well as their location along the corrugated struts was monitored based on XCT scans acquired subsequently to chemical etching, see [8] for a thorough analysis. It was shown that it is mandatory to avoid the presence of severe notch-like defects in the regions sustaining high tensile stresses, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The acquisition conditions can be optimized for each type of sample by selecting a suitable load-bearing bell. The DVC procedure has been successfully applied to a wide range of acquisitions: in situ nanotomography high-temperature tensile tests (Kumar et al, 2019), in situ micro-CT firn densification (Burr, 2017) and in situ unfolding of corrugated struts produced by additive manufacturing (Suard et al, 2020).…”
Section: Discussionmentioning
confidence: 99%